2022
DOI: 10.1007/s10389-022-01735-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of emotional eating and social media on nutritional behavior and obesity in university students who were receiving distance education due to the COVID-19 pandemic

Abstract: Aim This study aimed to evaluate the effects of emotional eating and social media on nutritional behavior and obesity in university students receiving distance education during the pandemic. Subject and methods This cross-sectional study was performed with 1000 undergraduate students who were receiving distance education due to COVID-19 in Türkiye. Data were collected using an online questionnaire that included demographic information, height, body weight, eating habits, the Scale of Effects of Social Media on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…This finding is consistent with previous research that has found a link between social media use and obesity ( 26 ). One possible explanation for this association is that social media use may lead to a sedentary lifestyle and unhealthy eating habits, which can contribute to weight gain and obesity ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous research that has found a link between social media use and obesity ( 26 ). One possible explanation for this association is that social media use may lead to a sedentary lifestyle and unhealthy eating habits, which can contribute to weight gain and obesity ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Six studies that assessed the increasing impact of sedentary time on weight gain during the COVID-19 pandemic [21,25,26,28,29,37], reduced sleep hours [20,27,52,54], increased Internet addiction during and after the pandemic [54], experienced barriers to weight management [57], length of confinement a day [40,42,60], long sitting hours [31,47,49,51], tobacco use [59], unnecessary alcohol conception [22,43], and long screen time use [27-29, 31, 41, 48] were reported as risk factors for high BMI. Another study reported female spend more time on social media [55].…”
Section: Sedentary Behaviour and Behavioural Lifestylementioning
confidence: 99%
“…The sample size ranged from 37 in Egypt [20] to 5,315,435 in South Korea [21]. The geographical distribution of the included articles was one in Belgium [22]], one in Brazil [23], one in Canada [24], one in Chile [25], five in China [26][27][28][29][30], three in the Czech Republic [31][32][33], one in Egypt [20], one in Indonesia [34], one in Israel [35], five in Italy [36][37][38][39][40], one in Jordan [41], one in Lebanon [42], one in Lithuanian [43], One in Morocco [44], one in the Netherlands [45], one in Saudi Arabia [46], four in South Korea [21,[47][48][49] three in Spain [50][51][52], one in Sri Lanka [53], three Turkey [54][55][56], one in the UK [57], and finally, three were conducted in the USA [58,59]. Quality was assessed using the modified Newcastle-Ottawa Scale [19].…”
Section: Description Of Included Articlesmentioning
confidence: 99%
“…Eating habits and behaviors can be changed due to sociobiological, psychological, biological and physiological factors ( 12 ), and studies have shown that situations with a context of prolonged stress, such as the COVID-19 pandemic, impact all these factors ( 13 , 14 ). In addition, social distancing caused changes in the behavior of individuals ( 15 ), and eating behavior was also affected by the economic and social crisis associated with the health emergency ( 16 ).…”
Section: Introductionmentioning
confidence: 99%